Surveillance of haemoprotozoan and haemorickettsial diseases of cattle of northern Kerala - Archana S Nair (Department Of Veterinary Epidemiology & Preventive Medicines,College of Veterinary And Animal Sciences, 2008)
A cross-sectional study was conducted to assess the carrier status of haemoprotozoan and haemorickettsial diseases of cattle of Northern Kerala. The diagnostic methods employed were microscopical examination of blood smears stained with Giemsa and Acridine Orange and polymerase chain reaction. A total of 150 blood samples were collected from the five districts of Northern Kerala (30 samples from each district). Microscopical examination of Giemsa stained smears revealed Theileria like piroplasms (41.2 per cent), Babesia piroplasms (2.6 per cent) and Anaplasma inclusions (1.3 per cent) while Acridine Orange stained smears detected Theileria like piroplasms in 47.2 per cent, Babesia piroplasms in 2.6 per cent and Anaplasma inclusions in 2 per cent of blood smears examined. Acridine Orange staining is more easy, time saving and reliable in detecting of haemoparasites than Giemsa staining technique. Polymerase chain reaction detected haemoprotozoan like T. evansi (34.6 per cent), B. bigemina (0.6 per cent), an uncharacterized Theileria organism (16 per cent) and T. orientalis (1.3 per cent). A. marginale (16.7 per cent) and A. bovis (3.3 per cent) were the haemorickettsial organisms detected by PCR. Mixed infections were detected in 16.6 per cent of the samples. T.annulata, B. bovis and A. phagocytophila were not detected in any of the samples. Polymerase chain reaction showed much higher sensitivity compared to examination of stained smears in detecting carrier animals. Trypanosomosis is the most prevalent protozoan disease among carrier animals of Northern Kerala which were detected only with the help of PCR while microscopy totally failed to detect such carriers. The high prevalence of haemoprotozoan and haemorickettsial diseases suggests the abundance of ticks and flies in Northern Kerala which acts as vectors for these parasites. Kannur and Palakkad districts revealed maximum prevalence of T. evansi. In addition, anaplasmosis was also widely prevalent in Palakkad district. Microscopical examination of blood smears from cattle of the hilly districts of Wayanad, Malappuram and Kozhikode revealed the presence of a Theileria like piroplasm which were not amplified with PCRs specific for Theileria genus, T. annulata or T. orientalis and this uncharacterized piroplasm needs urgent attention.